До історії повсякденності чернігівських ієрархів та про подорожі у сер. XVIII cт. - Травкіна, О. (Сiверянський лiтопис, 2015)
У статті на основі архівних джерел висвітлюється питання практики вилучення
грошей, культових предметів, посуду ієрархів сер. XVIII ст. після їхньої смерті та доправлення в Синод, а також перевезення цих речей і грошей, тобто детальної подорожі в цей час із Чернігова до Москви. В статье на основе архивных источников освещается вопрос практики изъятия
денег, культовых предметов, посуды иерархов серед. XVIII в. после их смерти и доставки в Синод, а также перевоз этих вещей и денег, то есть подробное путешествие в это время из Чернигова в Москву. On basis of archival source the article examines questions connected with a seizure of
money, cult-objects, tableware of hierarches of the middle of 18-th cent., after their death and
dispatch to Synod, and also conveyance of these things and money, in other words, detailed
journey of this period from Chernihiv to Moscow.
The recordation of money, silver, brazen and tin tableware of spiritual people who died,
was drawn up in 1753 as per administrative order of Synod, this list includes such names as:
Chernihiv bishop of Eletskiy Monastery Tymofiy Maksymovych, hegumen of Kostyanskyi
Trinity Monastery Toviy Smorzhevskyi and their dispatch to Synod. The article represents the
recordation of money and things of these hierarches, which are remain after their death and
characterize the mode of life and some aspects of their daily life.
Also, the article covers the route, amount of money and time, which were spent and wasted
for getting to a place money and things of hierarches from Chernihiv to Moscow and for a
return journey. The article represents that in the middle of 18-th cent. it was very difficult to
travel from Chernihiv to Moscow and it took considerable funds and time.